Computation of ground motion amplification in Kolkata megacity (India) using finite-difference method for seismic microzonation - Shiuly, Amit; Kumar, Vinay; Narayan, Jay (Acta Geophysica, 2014)
Abstract This paper presents the ground motion amplification scenario along with fundamental frequency (F 0) of sedimentary deposit for the seismic microzonation of Kolkata City, situated on the world’s largest delta island with very soft soil deposit. A 4th order accurate SH-wave viscoelastic finite-difference algorithm is used for computation of response of 1D model for each borehole location. Different maps, such as for F 0, amplification at F 0, average spectral amplification (ASA) in the different frequency bandwidth of earthquake engineering interest are developed for a variety of end-users communities. The obtained ASA of the order of 3–6 at most of the borehole locations in a frequency range of 0.25–10.0 Hz reveals that Kolkata City may suffer severe damage even during a moderate earthquake. Further, unexpected severe damage to collapse of multi-storey buildings may occur in localities near Hoogly River and Salt Lake area due to double resonance effects during distant large earthquakes.